Fear of being infected with COVID-19 virus among the medical social workers and its relationship to their future orientation - Snoubar, Yaser; Zengin, Oǧuzhan (Frontiers in Psychology, 2022)
COVID-19 has been studied extensively for its direct effects on healthcare workers. Despite this, very little is known about the effect of COVID-19 fear on future orientation. Studying medical social workers' fear of being infected with COVID-19 and their future orientation was the primary method used to examine this relationship. 204 Turkish medical social workers on the pandemic's front lines were included in the total sample. Social workers were found to be extremely concerned about contracting Covid-19. Although only gender is a significant predictor of the fear of contracting Covid-19 infection, the study also found that female social workers have a higher fear of infection than males. Also, no correlation exists between social workers' vaccination status and their fear of contracting Covid-19. There was a weak negative correlation between social workers' fear of contracting Covid-19 and their future orientation, but in general, social workers had a positive future orientation. Medical social workers and front-line health care providers can use these findings to develop effective and culturally appropriate intervention programs to reduce COVID-19 concerns and foster a forward-looking outlook.